Raising a Telecommunication Line Pole (TLP) / Muhammad Amin Ahmad Fauzi - Ahmad Fauzi, Muhammad Amin (Universiti Teknologi MARA, Perak, 2022)
Telecommunication poles are vital to perform communication on a daily basis. Therefore, this report will discuss how to install the poles from the beginning until the work is finished. This project was done at Pantai Hospital Klang, Port Klang, Selangor and fully supplied by DiGi telecommunication operator. The objectives of this report are mainly to understand the installation process of the telecommunication poles, boom and antenna while identifying all the machinery and tools used in the process. Other than that, this report will also state the problems that might occur during the process and how to solve them. There are three ways of collecting data in this report, namely by observation, interviewing with the person in charge and reading several documents to ensure all the data collected is prompted and can benefit others in the future.